Early Weaning and Milk Substitutes Affect the Gut Microbiome, Metabolomics, and Antibody Profile in Goat Kids Suffering From Diarrhea - Zhong, Tao; Wang, Cheng; Wang, Xinlu; Freitas-de-Melo, Aline; Zeng, Bo; Zhao, Qianjun; Zhan, Siyuan; Wang, Linjie; Cao, Jiaxue; Dai, Dinghui; Guo, Jiazhong; Li, Li; et al. (Frontiers in Microbiology, 2022)
Early weaning and milk substitutes increase the incidence of diarrhea in young ruminants, which may modify their gut microbiota, metabolism, immunity, and health. The aim of the study was to determine if early weaning and milk substitutes affect the gut microbiota, metabolism, and immunological status of goat kids suffering from diarrhea. The 16S rRNA gene and metagenomic sequencing in feces and serum metabolomics of early-weaned and artificially reared goat kids suffering from diarrhea (DK group) and healthy goat kids reared by their mothers (HK group) were analyzed. The serum biochemistry and immunoglobulin concentration were also determined. Several probiotics, such as Streptococcus and Lactobacillus, were higher in the feces of the DK group than in feces of the HK group. Ruminococcus sp. was elevated in the feces of HKs, likely being a biomarker for goat health. Taking all the carbohydrate-active enzyme (CAZyme) families into consideration, 20 CAZyme families were different between the groups. Compared with the DK group, the relative quantity of glycoside hydrolases (GH) and glycosyltransferase (GT) families in the HK group decreased. GT70 was only identified in HK kids participating in the activity of β-glucuronosyltransferase during the carbohydrate metabolism. Overall, 24 metabolites were different between the groups, which were mainly involved in protein digestion and absorption, cyanoamino acid metabolism, and cholesterol metabolism. The concentrations of immunoglobulins G and M were significantly lower in the DK than in the HK group. In conclusion, our study characterized the fecal microbiota, metabolism, and immunological status of early-weaned and artificially reared goat kids suffering from diarrhea.